Keefektifan Model PBL Berbantuan Media Fraction Smart Pirates Terhadap Kemampuan Pemecahan Masalah Siswa Kelas IV Sekolah Dasar - Hidayah, Rizqi Nur; Andrijati, Noening (Jurnal Gentala Pendidikan Dasar, 2025)
The aim of this study is to compare the mathematical problem-solving abilities of fourth-grade elementary school students who were taught emplpoying the Fraction Smart Pirates-supported Problem-Based Learning (PBL) model with those who were not. Additionally, the study will look into how this approach affects students' problem-solving skills in fraction topics. A quantitative experimental methodology was applied in this investigation. A pretest and a posttest were administered as the primary data collection tools. Numerous statistical tests, including the N-gain analysis, homogeneity test, normalcy test, as well as independent t-test, were employed to assess the data.The outcomes indicate that implementing the PBL model with the support of Fraction Smart Pirates effectively enhances students' mathematical problem-solving abilities in fraction material among fourth graders in the Diponegoro Cluster. This conclusion is supported by the outcomes of the independent t-test and N-gain analysis.